2022
DOI: 10.1002/asia.202200329
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Evaluation of Mutolide and Analogues

Abstract: The convergent total syntheses of three 14membered macrolide natural products, mutolide, nigrosporolide and (4S,7S,13S)-4,7-dihydroxy-13-tetradeca-2,5,8-trienolide have been achieved. The key synthetic features include Shiina macrolactonization to assemble the 14-membered macrocyclic core, Wittig or Still-Gennari olefination and selective reduction of propargylic alcohol to construct the Eor Z-olefins. Cross metathesis was also highlighted as an efficient tool to forge the formation of E-olefin. The three synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Our group has also recently disclosed the CFTR inhibitory activity of synthetic macrolide 7-9, in which mutolide (9) showed stronger inhibition (~70 % inhibition) compared to analogues 7 (40 % inhibition) and 8 (30 % inhibition) at the same concentration of 5 μM. [9] Disappointingly, synthetic 4 and 5 were found to show no effects on CFTR-mediated chloride secretion in T84 cells stimulated by forskolin (a cAMP donor) at both 5 and 10 μM compared to a positive control, CFTR(inh)-172 (Figure S77 in the Supporting Information). Therefore, the β-epoxide moiety of macrolides 4 and 5 apparently suppressed the CFTR inhibitory activity compared to compounds 7 and 8, which are their C5À C6 Zolefin counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has also recently disclosed the CFTR inhibitory activity of synthetic macrolide 7-9, in which mutolide (9) showed stronger inhibition (~70 % inhibition) compared to analogues 7 (40 % inhibition) and 8 (30 % inhibition) at the same concentration of 5 μM. [9] Disappointingly, synthetic 4 and 5 were found to show no effects on CFTR-mediated chloride secretion in T84 cells stimulated by forskolin (a cAMP donor) at both 5 and 10 μM compared to a positive control, CFTR(inh)-172 (Figure S77 in the Supporting Information). Therefore, the β-epoxide moiety of macrolides 4 and 5 apparently suppressed the CFTR inhibitory activity compared to compounds 7 and 8, which are their C5À C6 Zolefin counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has recently reported the in vitro cytotoxic activity of synthetic analogues of 4 and 5 , i.e. nigrosporolide ( 7 ), (4 S ,7 S ,13 S )‐4,7‐dihydroxy‐13‐tetradeca‐2,5,8‐trienolide ( 8 ) and mutolide ( 9 ) against three human cancer cell lines including HCT116 colorectal carcinoma, MCF‐7 breast adenocarcinoma and Calu‐3 lung adenocarcinoma using the MTT assay [9] . It was discovered that synthetic mutolide ( 9 ) was significantly active against the HCT116 colon cancer cells (IC 50 =12 μM) and was essentially inactive against the other two cell lines (IC 50 >50 μM), whereas macrolactone analogues 7 and 8 showed no cytotoxic effects on all three cancer cell lines tested.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations